A revision of the concept of Mago O. Pickard-Cambridge, 1882, and proposal of a new genus (Araneae: Salticidae: Amycini) - Ruiz, Gustavo R.s.; Maddison, Wayne P.; Galiano, Maria Elena (Zootaxa, 2019)
In this paper we redescribe the type species of Mago O. Pickard-Cambridge, M. intentus O. Pickard-Cambridge, and describe Mago brimodes Ruiz & Maddison sp. nov. from Ecuador. Based on both morphological features and the 16SND1 gene region, we concluded that the larger spiders traditionally identified as Mago, such as Mago acutidens Simon and related species, are not closely related to the small dark M. intentus (type species) and M. brimodes. Matinta Ruiz & Maddison gen. nov. is therefore proposed to hold most species previously included in Mago. The following species are transferred from Mago to the new genus: Matinta acutidens (Simon, 1900) comb. nov. (type species), Matinta apophysis (Costa & Ruiz, 2017) comb. nov., Matinta balbina (Patello & Ruiz, 2014) comb. nov., Matinta chickeringi (Caporiacco, 1954) comb. nov., Matinta delicata (Patello & Ruiz, 2014) comb. nov., Matinta fasciata (Mello-Leitão, 1940) comb. nov., Matinta fonsecai (Soares & Camargo, 1948) comb. nov., Matinta furcata (Costa & Ruiz, 2017) comb. nov., Matinta jurutiensis (Patello & Ruiz, 2014) comb. nov., Matinta longidens (Simon, 1900) comb. nov., Matinta mimica (Costa & Ruiz, 2017) comb. nov., Matinta opiparis (Simon, 1900) comb. nov., Matinta pardo (Costa & Ruiz, 2017) comb. nov., Matinta procax (Simon, 1900) comb. nov., Matinta saperda (Simon, 1900) comb. nov., Matinta silvae (Crane, 1943) comb. nov., Matinta similis (Patello & Ruiz, 2014) comb. nov., Matinta steindachneri (Taczanowski, 1878) comb. nov. and Matinta vicana (Simon, 1900) comb. nov. Mago dentichelis Crane, 1949 is transferred to Noegus Simon.